Digital Transformation in Fisheries Cultivation: Catfish Farmer Group Management Information System: Transformasi Digital dalam Budidaya Perikanan: Sistem Informasi Manajemen Kelompok Pembudidaya Lele - Ihsan, Hayatul; Efendi, Raimon; Yandani, Efri (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2024)
The development of a web-based management information system at Pokdakan Rangkiang Farm aims to improve the efficiency and effectiveness of fisheries cultivation data management. By switching from manual recording methods that are prone to errors and difficulties in tracking data, this system is designed to provide structured digital recording and facilitate access to information. This study uses the Black Box Testing method to ensure that all system functions run well, which shows positive results in admin and user testing. The implementation of this system not only improves the accuracy of data management but also supports environmentally friendly cultivation practices through real-time water quality monitoring using Internet of Things (IoT) technology. In addition, this system allows for deeper data analysis, which is important for better decision making in fisheries cultivation. Thus, this information system is expected to make a significant contribution to the sustainability of fisheries cultivation businesses and improve community welfare. This study is in line with previous findings showing that information technology can increase productivity and sustainability in the aquaculture sector, as well as support the achievement of sustainable development goals.